Исследование получения синтез-газа для производства аммиака и метанола - Шульга, Игорь Владимирович; Гринь, Григорий Иванович; Кутовой, Дмитрий Сергеевич; Эйхман, Виталий Алексеевич; Зеленский, Олег Иванович (НТУ "ХПИ", 2017)
Исследован метод получения сырья для синтеза аммиака и метанола газификацией березовой щепы, отходов углеобогащения, полукокса, малометаморфизованных углей. Изучены разные размеры частиц, температура, времени пребывания в реакторе при различных окислителях, сделан вывод о экономичности и целесообразности использования газификации как метода получения сырья для производств синтеза аммиака и метанола. Было оценена пригодность генераторного газа для синтеза аммиака и метанола. Результаты исследований, при внедрении в реальное производство, могут дать экономический эффект в химической промышленности.

Methods of receiving raw materials for synthesis of ammonia and a methanol are offered by gasification of birch spill, of wastage of coal preparation, of semi-coke, of the low-metamorphosed coals are considered, researches were conducted at various ranges of particle sizes, temperatures, a response time in the reactor and at various blasting, the conclusion is drawn on profitability and expediency of use of gasification as method of receiving raw materials for synthesis of ammonia and a methanol. Data obtained and researched in this article prove, that for synthesis of ammonia is suitable producer gas after gasification of semi-coke and of the low-metamorphosed coals but after minor correction of aspect ratio. For synthesis of methanol is suitable producer gas after gasification of birch spill and of wastage of coal preparation, but the serious correction of aspect ratio is needed. The suitability of the producer gas for the synthesis of ammonia and methanol has been estimated. Results of this scientific article are applicable for synthesis of ammonia and methanol. There are reasons for creation of an experimental industrial plant for confirmation of those results in industrial scale. After confirmation on an experimental industrial plant and adjustment of data offered technology of gasification can be implanted into production. Choice of raw materials depends on final product and availability of raw materials. The researches conducted in this article can increase economic potential in chemical industry.
Research of receiving synthes gasis for production of ammonia and a methanol
Keywords: газификация; твердое топливо; генераторный газ; химическая промышленность; экономический эффект; gasification; semi-coke; low-metamorphosed coals; birch spill; coal preparation wastage